Watch Where You're Going? Interferer Velocity and Visual Behavior Predicts Avoidance Strategy During Pedestrian Encounters. Issue 4 (4th July 2018) - Croft, James L.; Panchuk, Derek
ABSTRACT: Pedestrians can avoid collisions with other pedestrians by modifying some combination of their velocity and their path. The authors investigated how path constraints (constrained or unconstrained), interferer velocity (slow or fast), and vision (looking or not looking; time spent looking at the interferer) influenced collision avoidance to an oblivious interferer walking on a perpendicular path. Ten participants walked 6 m to either a point or line target on either a constrained or unconstrained path while wearing an eye-tracking device and avoiding an oblivious interferer that walked at 2 speeds. Looking behavior and interferer velocity were reliable predictors of determining whether a pedestrian would pass in front of or behind the interferer, while path constraints were less reliable. These findings highlight the degeneracy in human movement systems and suggest that, in complex environments, behavior may not always be optimized for efficiency.